An assessment of middle-class stability through the determinants of income polarization: Evidence from a multinational panel study - GJACI, Blerina; KRISTO, Suela (Edelweiss Applied Science and Technology, 2025)
This paper explores the factors influencing income polarization, which serves as a proxy indicator for assessing the stability of the middle class in South-East and Central-East European countries. The study employs an unbalanced panel dataset covering 16 countries over the period 1996–2022 to examine how key economic and social factors, including GDP per capita, remittances, unemployment, urbanization rate, tertiary education enrollment, and social protection expenditures, affect income polarization. Modeling the polarization index as a function of socioeconomic factors represents an innovative approach inspired by empirical frameworks that traditionally explain income inequality through the Gini index. The aim is to demonstrate that the polarization index can effectively capture the stability and strength of the middle class. The results reveal that GDP per capita and unemployment are the most significant determinants, both positively associated with income polarization. This indicates that when economic growth is not inclusive and unemployment rises, income distribution becomes more uneven, resulting in a more polarized society and a shrinking middle class. The study contributes to the literature on middle-class dynamics and income inequality, emphasizing the importance of inclusive growth and employment-oriented policies for enhancing social stability.